2019
DOI: 10.1136/neurintsurg-2019-014936
|View full text |Cite
|
Sign up to set email alerts
|

MRA versus DSA for the follow-up imaging of intracranial aneurysms treated using endovascular techniques: a meta-analysis

Abstract: BackgroundTreated aneurysms must be followed over time to ensure durable occlusion, as more than 20% of endovascularly treated aneurysms recur. While digital subtraction angiography (DSA) remains the gold standard, magnetic resonance angiography (MRA) is attractive as a non-invasive follow-up technique. Two different MRA techniques have traditionally been used: time-of-flight (TOF) and contrast-enhanced (CE) MRA. We analysed data from studies comparing MRA techniques with DSA for the follow-up of aneurysms und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 87 publications
0
29
0
2
Order By: Relevance
“…Studies such as PFLEX 20 , PITA 1 and PUFS 5 employed DSA as the follow-up modality for PED-treated aneurysms. There has been widespread adoption of flow-diverter devices with a range of follow-up methods and time points and a recent meta-analysis that compared MRA and DSA concluded that both 3D-TOF-MRA and contrast-enhanced MRA can be used reliably to follow up flow-diverter devices 30 . The sensitivity and specificity of TOF-MRA were 86% and 95%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies such as PFLEX 20 , PITA 1 and PUFS 5 employed DSA as the follow-up modality for PED-treated aneurysms. There has been widespread adoption of flow-diverter devices with a range of follow-up methods and time points and a recent meta-analysis that compared MRA and DSA concluded that both 3D-TOF-MRA and contrast-enhanced MRA can be used reliably to follow up flow-diverter devices 30 . The sensitivity and specificity of TOF-MRA were 86% and 95%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of IAs mainly depends on imaging diagnostic methods, such as magnetic resonance angiogram (MRA), computed tomography angiography (CTA), and digital subtraction angiography (DSA) [49]. Despite the fact that preoperative diagnosis has improved in recent years, overall prognosis remains poor, and SAH remains a serious health problem.…”
Section: Lncrnas As Non-invasive Biomarkersmentioning
confidence: 99%
“…Other limitations are that follow-up was relatively short (mean follow-up 5 months and 15 months) and 3D TOF MRA was used for follow-up in two cases. Whilst a recent metaanalysis has shown that MRA (whether using TOF MRA or CEMRA) is a reliable modality for the follow-up of aneurysms treated using a variety of endovascular techniques (including stent-assisted coiling and flow diverters), 23 it is possible that there was a reduction in sensitivity compared to DSA in detecting aneurysmal remnants according two small retrospective studies where WEB susceptibility was described. 24,25 It is conceivable that the adequate occlusion rates observed in our series could be lower.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%